Las ventajas y desventajas de fusionar las empresas del estado colombiano (2010)
Without doubt the major benefitted with the fusions of the companies of the Colombian State, is this same one, are been worth the figures of the economic crises of the fused companies, as well as the administrative inefficiency of the same, despite the fusion has its benefits as it is the resurgence of new companies, where the State can rectify the errors committed in the past, I analyze a practical case of the real life that it contextualises to the reader in the understanding of the meaning of the fused companies